A Simple Technique to Prevent Early or Late EndoButton Deployment in Anterior Cruciate Ligament Reconstructions: A Technical Note - Fogagnolo, Fabricio; Salim, Rodrigo; Kfuri, Mauricio (The Journal of Knee Surgery, 2018)
The use of suspensory graft fixation methods in arthroscopic reconstruction of the anterior cruciate ligament has become increasingly popular with the more frequent use of tendon grafts and anatomical techniques involving the creation of bone tunnels. An important technical step to ensure adequate fixation of the graft when using EndoButton-type implants, particularly in the femur, involves flipping the EndoButton plate at the correct length to avoid performing this maneuver before the appropriate time or leaving soft tissue between the plate and lateral cortex of the femur. In the present study, we describe a simple arthroscopic technique for indicating the correct time to flip/deploy the EndoButton plate.
Keywords: EndoButton; ACL reconstruction; femoral tunnel; graft